Pengaruh Media Kalender Belajar Obat Bebas Terbatas terhadap Pengetahuan dan Sikap Remaja dalam Mewujudkan Gema Cermat - Fadli Fadli; Agustini Agustini (Syntax Corporation Indonesia, 2021)
Along with changes in the lifestyle of people who tend to pay less attention to health, the development of disease in the community is inevitable. This problem can be overcome by providing education about medicine through smart calendars to the public. Calendar is not only designed to improve thinking skills but also to stimulate youth thinking, including the ability to concentrate and solve problems on changes in knowledge and action. The purpose of this study was to determine whether there was an effect of the Smart Calendar Media for Learning limited free drugs on Knowledge and Attitudes in Realizing a Smart Community Movement Using Drugs. This research was conducted with a quantitative survey method by collecting data via a google form. The sampling method uses a side probability with a simple random sampling technique. Sampling was conducted on 140 adolescents at SMA Negeri 1 Kendawangan, then obtained a sample of 103 respondents. Data analysis used the Kolmogorov-Smirnov test for normality, Wilcoxon test for hypothesis testing of knowledge and attitudes.sig (2-tailed) value for knowledge and attitude is 0,000. The conclusion of this study is that the smart calendar method can affect adolescent knowledge and attitudes about limited free drugs.